Bilateral Extensive Port-Wine Stain(Naevus Flammeus) With Persistent Aberrant Mongolian Spots : Phakomatosis Pigmentovascularis Type II a In A Nepalese Girl - Joshi Arun; Prasad Sah Shaturghan; Agrawal Sudha C; Agarwalla Arun; Jacob Mary (Wolters Kluwer Medknow Publications, 2000)
An 11 year old girl had extensive port-wine stain affecting here trunk and limbs bilaterally and persistent Mongolian spots on her trunk and buttocks since birth. Combination of such congenital cutaneous vascular and pigmentary anomalies is known as phakomatosis pigmentovascularis (PPV) and we report the first such case form Nepal.